2019
DOI: 10.1589/rika.34.79
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-Day Effects on Dynamic Postural Control

Abstract: The purpose of this study was to investigate the effect of time-of-day (early morning vs evening) on dynamic balance control using posturography and electromyography. [Participants and Methods] Nine healthy individuals participated in this study. They performed the Cross Test, moving the center of pressure (COP) laterally and longitudinally on a force plate with their eyes open and closed. The electromyograms (EMGs) from the anterior tibialis, and the medial and lateral gastrocnemius were simultaneously record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several studies have reported that high CV during gait is associated with poor postural con-trol 18,19 ) . Moreover, many studies of diurnal patterns have shown that postural control ability fluctuates with time and declines in the morning [20][21][22] . However, another study evaluated postural control and reported no difference in the ability in the morning and daytime 23,24) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that high CV during gait is associated with poor postural con-trol 18,19 ) . Moreover, many studies of diurnal patterns have shown that postural control ability fluctuates with time and declines in the morning [20][21][22] . However, another study evaluated postural control and reported no difference in the ability in the morning and daytime 23,24) .…”
Section: Discussionmentioning
confidence: 99%